VILLAGE POTENTIAL PRIORITIZATION DECISION SUPPORT SYSTEM SAW METHOD - Susanti Kaka; Gergorius Kopong Pati; Karolus Wulla Rato (JTH: Journal of Technology and Health, 2023)
Village development is an effort to improve the quality of life and life for the greatest welfare of village communities. Meanwhile, the aim of village development is stated in article 78 paragraph 1, namely improving the welfare of village communities and the quality of human life as well as overcoming poverty through fulfilling basic needs, developing village facilities and infrastructure, developing local economic potential, and using natural resources and the environment in a sustainable manner. As is the case with village development, Watu Wona Village is one with a majority of farmers, which is an example of a road access development plan that really needs assistance from the government in its construction to support the production and sale of agricultural products. Infrastructure is still lacking, damaged infrastructure roads make access to the village difficult. As a result, the flow of goods and services to villages to transport agricultural products is also lacking and hampered. Based on the existing problems, village development planning is needed using a decision support system (SPK) so that village selection in Watu Wona village is faster and more accurate. By using the SAW method comparison